PENERAPAN TEKNOLOGI PENGOLAHAN SAMPAH ORGANIK RUMAH TANGGA DENGAN MAGGOT PADA PROGRAM KAMPUNG IKLIM DI KOTA BUKITTINGGI - Febriamansyah, Rudi; Febria, Fuji Astuti; Yulistriani, Yulistriani; Rahman, Defri; Mahdi, Mahdi; Rahayu, Resti (Jurnal Hilirisasi IPTEKS, 2021)
This activity is motivated by concern for the facts of climate change occurring globally and regionally. The agreement of many countries to address this change problem has been initiated since 1990, until the most recent high-level meeting "climate adaptation summit" in 2020. The Intergovernmental Panel on Climate Change (IPCC) warned that there are only 12 years left or until 2030 to prevent extreme climate disasters that occur due to global warming with a maximum temperature increase of 1.5Â°C. In response to this, the Indonesian government has also taken a number of concrete steps in all aspects of climate change adaptation and mitigation, both at the local, regional and national levels. One of the national programs that directly touch local communities is the climate village program or known as "PROKLIM". The city of Bukittinggi has actively responded to this national program, so that two of the three climate villages developed by the Environmental Service of the city of Bukittinggi have received national awards for the achievements of their community group activities. This activity is one of the activities that is of interest to community groups in one of the climate villages in Bukittinggi City, because it sees the potential to overcome the problem of relatively high organic waste generation both in the village itself and in the nearest market location, with the use of larvae (maggot) from Black Soldier Fly which can be done in groups. It is hoped that organic waste management with the use of larvae (maggot) will not only overcome the problem of organic waste, but also at the same time increase people's income, both from selling the maggot products to fish/poultry farmers, as well as being able to be used by group members for their own business. fisheries and livestock.